Does supply chain integration mediate the relationships between product/process strategy and service performance? An empirical study - Droge, Cornelia; Vickery, Shawnee K.; Jacobs, Mark A. (International journal of production economics, 2012)
Determining the antecedents and performance consequences of supply chain integration is a key focus of recent supply chain management research. This study investigates the role of supply chain integration in mediating the effects of product and process modularity strategies on service performance. Adaptive Structuration Theory (AST) provides the theoretical context. The study provides empirical support for the importance of considering product and process strategies in understanding the impact of integration on performance. Canonical correlation analysis and effects decomposition are used to test the research model. The results demonstrate that customer integration mediates the linkages from product modularity and process modularity to delivery performance, as well as mediating the relationship between process modularity and support performance. In contrast, supplier integration mediates the relationship between process modularity and delivery performance only. The overall lack of support for a direct relationship between process modularity and service performance suggests that modular processes (1) lack intrinsic interfaces such as those found in modular product architectures and (2) rely upon integration to fill the role of interface. Product modularity and process modularity are both shown to be related to supplier integration and customer integration, suggesting that they engender integration across a supply chain.